Rosai–Dorfman disease involving gallbladder and liver—Report of a case. (2015) - Arabadzhieva, Elena; Yonkov, Atanas; Bonev, Sasho; Bulanov, Dimitar; Taneva, Ivanka; Pirdopska, Tatyana; Terziev, Ivan; Dimitrova, Violeta
Highlights: Rosai–Dorfman diseasе (RDD) is a rare histiocytic disorder оf unclear etiology. RDD is characterized by emperipolesis and presence of S-100 positive histiocytes. RDD usually presents as a massive, bilateral enlargement of the neck lymph nodes. Localization of RDD in the liver and gallbladder is extremely rare. Treatment is recommended in cases with symptomatic localized or extended RDD. Abstract: Introduction: Rosai–Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy, is a rare histiocytic disorder of unclear etiology. Lymphadenopathy commonly affects the lymph nodes of the neck and the head, but extranodal involvement has been observed too. Presentation of case: We describe an unusual case of RDD with involvement of the gallbladder, liver and cystic lymph node, clinically manifested as an exacerbated cholecystitis. The patient underwent a cholecystectomy with atypical liver resection because the finding was macroscopically suspected of gallbladder cancer. The diagnosis of RDD was confirmed by immunohistochemical study. Discussion: Histological features of RDD include histiocytic proliferation, emperipolesis and positive immunostaining for S-100 protein and typically negative for CD1a. Gastrointestinal localization of RDD, especially in the liver and pancreas, is extremely rare. Typically, the liver is affected as a part of systematic spread of RDD. We have not found reports for involvement of the gallbladder. Conclusion: The presented case is valuable due to its rarity and difficulty in differential diagnosis.